First beam test of a liquid Cherenkov detector prototype for a future TOF measurements at the Super-FRS - Kuzminchuk-Feuerstein N. A. Natalia Aleksandrovna; Ferber N. Nadine; Fiks E. I. Elena Ivanovna; Kaufeld I. Ingo; Voss B. Bernd (2017, 2017)
Title screen